A Refinement to the Viterbi-Viterbi Carrier Phase Estimator and an Extension to the Case With a Wiener Carrier Phase Process - Li, Y. (Institute of Electrical and Electronics Engineers Inc., 2021)
10.1109/ACCESS.2019.2922313